2004
DOI: 10.1089/088922204323087705
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Molecular Epidemiology of HIV Type 1 among Northern Thai Drug Users, 1999 to 2002

Abstract: CRF01_AE and subtype B have dominated the HIV-1 epidemic in Thailand since 1989. We reported a new circulating recombinant form of HIV-1, CRF15_01B, as well as other unique CRF01_AE/B recombinants among prevalent HIV infections in Thailand. We sought to study this challenging molecular picture through assessment of subtypes among recent HIV-1 seroconverters in northern Thai drug users. A total of 847 HIV-1 seronegative drug users (342 IDU and 505 non-IDU) were enrolled, from 1999 to 2002, in a prospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 34 publications
4
66
2
Order By: Relevance
“…First, it was noted that the withinsubtype interhost genetic divergence had increased significantly compared to that noted in earlier surveys (9,10,17,(22)(23)(24)(25). Second, the barriers that maintained the segregation of subtypes on the basis of risk factors started to efface; the representation of CRF01_AE among IDUs increased, especially among new infections (26), to the point where CRF01_AE accounted for 80 to 90% of the cases in Bangkok and the northern province of Chiang Mai (27,28). Coinfections (29) and superinfections (30) with subtype B and CRF01_AE were documented, and intersubtype recombinants were detected among individuals with either IDU (28,31) or heterosexual (32,33) exposure.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…First, it was noted that the withinsubtype interhost genetic divergence had increased significantly compared to that noted in earlier surveys (9,10,17,(22)(23)(24)(25). Second, the barriers that maintained the segregation of subtypes on the basis of risk factors started to efface; the representation of CRF01_AE among IDUs increased, especially among new infections (26), to the point where CRF01_AE accounted for 80 to 90% of the cases in Bangkok and the northern province of Chiang Mai (27,28). Coinfections (29) and superinfections (30) with subtype B and CRF01_AE were documented, and intersubtype recombinants were detected among individuals with either IDU (28,31) or heterosexual (32,33) exposure.…”
mentioning
confidence: 95%
“…Second, the barriers that maintained the segregation of subtypes on the basis of risk factors started to efface; the representation of CRF01_AE among IDUs increased, especially among new infections (26), to the point where CRF01_AE accounted for 80 to 90% of the cases in Bangkok and the northern province of Chiang Mai (27,28). Coinfections (29) and superinfections (30) with subtype B and CRF01_AE were documented, and intersubtype recombinants were detected among individuals with either IDU (28,31) or heterosexual (32,33) exposure. While most of the recombinants were URFs, a new CRF, CRF15_01B, was found throughout the country among individuals with either risk factor, reinforcing the linkage between the different epidemics in Thailand (31,32).…”
mentioning
confidence: 99%
“…Subtype A (sub-subtypes 1 and 2) strains are highly predominant in Kenya, with one study showing 93% of all strains found in the region being subtype A or a recombinant containing subtype A (Dowling et al, 2002). In addition, CRF01_AE is one of the major strains found in Thailand and Southeast Asia (McCutchan et al, 1992;Tovanabutra et al, 2004). Subsubtype A2 was first identified from sequences originating in the Democratic Republic of Congo and Cyprus (Gao et al, 2001), and is now also found in Kenya (Visawapoka et al, 2006).…”
Section: The Global Distribution Of Hiv-1 Subtypes and Crfsmentioning
confidence: 99%
“…Other South East Asian (SEA) countries, proximal to China, have also experienced similar epidemiological shifts, for example Thailand [18]. China is also no exception to this phenomenon and currently the Chinese HIV epidemic is dominated by high prevalence of a variety CRFs [7,19].…”
Section: Hiv Recombination In China and Sur-rounding Regions: It's Romentioning
confidence: 99%